E-Learning Is Not Inferior to On-Site Teaching in a Psychiatric Examination Course - Rauch, Christoph; Utz, Janine; Rauch, Miriam; Kornhuber, Johannes; Spitzer, Philipp (Frontiers in Psychiatry, 2021)
Background: Implementing e-learning into medical education is a growing field of research. Researchers have had positive experiences so far and evidence suggests it to be no less effective than offline teaching. However, there are few findings concerning psychiatric education and the use of simulated patients online. Methods: We developed an online workshop for medical students at our psychiatric clinic, including group work exercises, lectures and interviews with simulated patients. To compare the learning outcome, a cohort of students learning online was compared to a previous cohort that learned on-site. The same objective structured clinical examination (OSCE) was used in both cases. Evaluation questionnaires were gathered from students and lecturers and were compared to the former semesters along with the exam results. Results: The exam grades did not significantly differ between on-site and online teaching, even though students rated their own communication skills better with online teaching. We also found that the connection experienced between students and teachers was impaired without on-site contact. Discussion: We conclude that an online course may be an effective alternative to on-site teaching but requires further improvement to maintain a dependable student-teacher-relationship.